Superbike services management system (SSMS) - Mohd Fauzan, Mohd Zain (2015)
Nowadays, the increasing growths of superbike user in this country make a new trend for the people to having a new superbike. As we known, the services of any big bike also like services to the cars. A person who has a big bike also wants to make sure his big bike in good condition, so that they can travel to any place with safely without any trouble especially in engine condition. This is important to them because once problem happen to theirs big bike mays cause the cost for the services will be higher. To make sure engine of bike in good condition they must make some services at right time on when they must do the services. They will also know the cost of services and also will be tell about what services that will be do for his bike. So, the ways to help user of bike to manage theirs bike services is by using this system. This system will help user to book their services packages by ordering it through web system, moreover user also will know the charge of all packages because the packages will also tell user about pricing of that services. Furthermore, when the services already book by user, then they must send their bike to the center services. After the services already done by center, they will tell the user to pick up his bike and the next date of services will be send to the customer by SMS.